Biological Functions of Dillenia pentagyna Roxb. Against Pain, Inflammation, Fever, Diarrhea, and Thrombosis: Evidenced From in vitro, in vivo, and Molecular Docking Study - Sultana, Nahida; Chung, Hea-Jong; Emon, Nazim Uddin; Alam, Safaet; Taki, Md. Tohidul Islam; Rudra, Sajib; Tahamina, Afroza; Alam, Rashedul; Ahmed, Firoj; Mamun, Abdullah Al (Frontiers in Nutrition, 2022)
Dillenia pentagyna Roxb. is traditionally used to treat cancer, wound healing, diabetes and diarrhea in local tribes. This study was designed to evaluate the pharmacological potentiality of this plant. In vivo analgesic, anti-inflammatory and antipyretic studies of the methanol extracts of the D. pentagyna leaves (MEDP) were performed by using acetic acid-induced nociception, formalin-induced paw licking, and yeast induced pyrexia assay methods respectively. In vivo antidiarrheal activity was carried out in mice by following castor oil-induced diarrhea and gastrointestinal transit manner. In vitro thrombolytic experiment was performed employing the clot lysis activity. Besides, a molecular docking study was performed by executing the software (PyRx, Discovery Studio and UCSF Chimera). In the acetic acid-induced writhing study, MEDP possesses significant writhing inhibition in a dose-dependent manner. It showed 50.86% of maximum inhibition of pain in the case of MEDP at a dose of 400 mg/kg; body weight. In the anti-inflammatory study, maximum inhibition rate was observed at a value of 59.98% and 41.29% in early and late phases, respectively, at the dose of 400 mg/kg;b.w. In the case of yeast induced hyperpyrexia, MEDP reduced hyperpyrexia in a dose-dependent manner. In the antidiarrheal assay, MEDP moderately inhibited the occurrence of diarrhea in all the experiments. In the thrombolytic study, a moderate (17.76%) clot lysis potency has been yielded by MEDP. Again, the molecular docking simulation revealed strong binding affinities with almost all the targeted proteins. The present study suggests that the MEDP possesses remarkable pharmacological activity and this finding validated the ethnobotanical significance of D. pentagyna as the source of pain, fever and diarrhea management agent.